AVALIAÇÃO DAS DENSIDADES DE ESTOCAGEM DE Pomacea bridgesi E Pomacea lineata (MOLLUSCA GASTROPODA), SOB CONDIÇÕES DE LABORATÓRIO - Lima, Severino Adriano de Oliveira; Barros, José Carlos Nascimento de (Revista Nordestina de Zoologia, 2012)
Ahead of the continuous increase in population taxes and with the reduction of the availability of the products of if fishes, the demand of other food sources come increasing. In this way, each time is observed more the exploration of not traditionally commercialized not conventional animal species and. It enters the animals with great potential as food, meet the pertaining clams to the Pomacea sort (Perry, 1810) the they are rich in essential proteins, carbohydrates, fats, glycogen and amino acids. The species Pomacea lineata (Spix. 1827) and Pomace bridgesi (Reeve, 1856) are gastropods of the Ampullaridae family, had been used by presenting high taxes of reproduction, high taxes of growth and precocious sexual maturity, characteristic of the majority of the cultivated aquatic organisms and for if dealing with used sufficiently rustics animals already as food for the populations of Trinidade, Guianas and north and northeast of Brazil. This work had as objective to evaluate the performance of species P. lineate and Pomacea bridgesi cultivated in different densities of stockade with purpose lo demonstrate the viability of production of these species for aquiculture. The units of Pomacea bridgesi had presented development better and revealed more sensible to the experiment without interference in the development will have remained the quality of the water. The studied species had presented excellent alimentary conversion that was not influenced by the treatments more was differentiated between the species, with the Pomacea bridgesi having gotten the best ones resulted.